Analisis Konsep Sejarah Masa Penjajahan Bangsa Eropa pada Siswa Sekolah Dasar - Siti komala Putri; Sofian Abdulatif; Tin Rustini (Departement of Mathematics Education, 2022)
This article discusses the analysis of the concept of historical material during the European colonial period for elementary school students. It aims to analyze the concept of historical material during the European colonial period in elementary schools that is in accordance with the level of understanding of elementary level students. In compiling this article, the author collected data using quantitative methods. From the findings of the concept of historical material during the European colonial period for elementary school students, starting from exploring the ocean to look for spices to the arrival of Europeans to Indonesia to get spices. However, over time these Europeans began to arbitrarily occupy the government in Indonesia and make the Indonesian people miserable.